Sembilan Nilai Utama Gus Dur Perspektif Etika Ibnu Miskawaih - Ahmad Yani Fathur Rohman (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2023)
K.H. Abdurrohman Wahid or who is familiar with the name Gus Dur is an important figure in Indonesia. Gus Dur is a figure who represents the santri group with its salaf traditions and also the intellectuals in the world of academia. People who loved Gus Dur voluntarily set up organizations or forums to channel aspirations and explore Gus Dur's values. So that in the teachings of the Gus Durian community there is the term Gus Dur's nine main values. These nine main values ​​are the hallmark and identity of the Gus Durian community. These nine main values ​​are the efforts of the Gus Durian community to find and formulate the values ​​of Gus Dur's struggle. Gus Dur's nine main values ​​are monotheism, humanity, justice, equality, liberation, simplicity, brotherhood, chivalry, and local wisdom. Gus Dur's nine main values ​​are ethical teachings practiced by Gus Dur to defend minorities. Gus Dur's teachings are very relevant to the ethical teachings of Ibn Miskawaih. Ibn Miskawaih himself is a major philosopher in Islam whose style of thought is influenced by Islamic religious concepts and Greek philosophical concepts. With these two features, Ibn Miskawaih's philosophy is comprehensive, especially in terms of ethics. The ethical teachings focus on understanding and cultivating character when carrying out an action. His views on ethics are related to human virtues, namely morals. This morality is divided into three parts, namely: wisdom, courage and chastity. These three virtues are born from a just attitude. Thus, there is compatibility between Gus Dur's teachings through Gus Dur's nine main values ​​and the ethical teachings of Ibn Miskawaih. Thus it can be concluded that there is a relationship between Gus Dur's nine main values ​​and the ethical teachings of Ibn Miskawaih.